Culture of patient safety in hospital units of gynecology and obstetrics: a cross-sectional study - Juliana Maria Almeida do Carmo; Isabel Yovana Quispe Mendoza; Vania Regina Goveia; Kleyde Ventura de Souza; Bruna Figueiredo Manzo; Gilberto de Lima Guimarães
ABSTRACT Objectives: to assess the patient safety culture of the health team working in three maternity hospitals. Methods: observational, cross-sectional, comparative study. 301 professionals participated in the study. The Hospital Survey on Patient Safety Culture questionnaire validated in Brazil was used. For data analysis, it was considered a strong area in the patient safety culture when positive responses reached over 75%; and areas that need improvement when positive responses have reached less than 50%. To compare the results, standard deviation and thumb rule were used. Results: of the 12 dimensions of patient safety culture, none obtained a score above 75%, with nine dimensions scoring between 19% and 43% and three dimensions between 55% and 57%. Conclusions: no strong dimensions for safety culture were identified in the three maternity hospitals. It is believed that these results may contribute to the development of policies that promote a culture of safety in institutions.